Return and reintegration: Conflicting priorities between political demand and development policy principles - Nadine Biehler; Amrei Meier (Stiftung Wissenschaft und Politik (SWP), 2019)
In Germany there is broad agreement that rejected asylum seekers and other persons obliged to leave the country should do so as soon as possible. Deportations, however, are complex, expensive and particularly controversial when the country of origin's political and security situation is fragile and unsafe. To incentivise voluntary return, the German government has expanded its programmes that facilitate return and complemented them with local reintegration measures, to be implemented by development actors. Non-governmental organisations have criticised this blending of migration and development policy objectives. Aside from this normative debate, however, there is too little discussion of the extent to which development programmes are suitable for meeting the individual and structural challenges of return, if at all.
Keywords: 320